2012
DOI: 10.1111/j.1748-5967.2011.00439.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and analysis of natural compounds from silkworm pupae and effect of its extracts on alcohol detoxification

Abstract: Silkworm pupae have much potential and many applications as a natural medicine to promote human health. However, their chemical components have not been fully characterized or understood. HPLC analysis was conducted to determine the content ratio (%) of individual amino acids in total protein of the pupae. It showed that glutamic acid (18.3%), histidine (14.6%) and alanine (10.2%) are the most common amino acids in silkworm pupae. Fatty acid composition of silkworm pupae oil was revealed by high‐pressure liqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…The SWP contained n-3 FAs, especially α-linolenic acid (36.3%), as a major component (Tomotake et al 2010). Kwon et al (2012) also reported that FA composition of SWP oil revealed a high ratio of EFAs (α-linolenic acid + linoleic acid; 49.0%) and non-essential FAs (19.9% oleic acid, 2.5% palmitoleic acid, 19.7% palmitic acid, 8.6% stearic acid and 0.3% eicosapentaenoic acid).…”
Section: Chemical Compositionmentioning
confidence: 99%
“…The SWP contained n-3 FAs, especially α-linolenic acid (36.3%), as a major component (Tomotake et al 2010). Kwon et al (2012) also reported that FA composition of SWP oil revealed a high ratio of EFAs (α-linolenic acid + linoleic acid; 49.0%) and non-essential FAs (19.9% oleic acid, 2.5% palmitoleic acid, 19.7% palmitic acid, 8.6% stearic acid and 0.3% eicosapentaenoic acid).…”
Section: Chemical Compositionmentioning
confidence: 99%
“…We found that the GFM contained various components, including several fatty acids (PA, HA, and LA), which accounted for 98.76% of all molecules and are believed to be the active components promoting ethanol metabolism (Kwon and others ). Tachiyashiki and Imaizumi () reported that C18‐unsaturated fatty acids (oleic acid, LA, and linolenic acid) may delay the elimination rate of gastric ethanol and lessen the increase in plasma ethanol concentration.…”
Section: Resultsmentioning
confidence: 97%
“…The most abundant compounds in GFM were PA (30.00%), methyl linoleate (34.10%), and LA (34.66%), accounting for about 98.76% of the GFM. Table shows 4 biologically active molecules (PA, HA, methyl linoleate, and LA), which may have varying antioxidant or alcohol metabolic activities (Beeharry and others ; Kumar and others ; Kwon and others ). The consequences of ethanol metabolism may result in the formation of harmful components, such as highly reactive oxygen‐containing molecules (ROS) that can damage liver tissues (Koop ).…”
Section: Resultsmentioning
confidence: 99%
“…Lassoued et al () also found that the DPPH radical scavenging activity of Neutrase hydrolysis with the lowest DH (11%) was higher than for Alcalase hydrolysis which had the highest DH (22%). Moreover, the high antioxidant activity of Neutrase hydrolysis may have been due to other antioxidants such as quercetin and riboflavin (B 2 ) which were found in silkworm extract by Kwon et al (). Therefore, the protein hydrolysate from Neutrase treatments had the best performance of antioxidant activity.…”
Section: Resultsmentioning
confidence: 99%
“…Protein from insect could provide a similar energy content to meat protein (Sirimungkararat, Saksirirat, Nopparat, & Natongkham, ). Moreover, insects contained some other nutrients such as fatty acid, vitamins, and minerals (Kwon et al, ).…”
Section: Introductionmentioning
confidence: 99%